2021
DOI: 10.33024/jmm.v5i2.4155
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN EKSTRAK DAUN KELOR (Moringa oleifera) TERHADAP KADAR HEMOGLOBIN PADA TIKUS PUTIH (Rattus norvegicus) GALUR WISTAR JANTAN

Abstract: Hemoglobin merupakan suatu protein tetrametrik eritrosit yang tersusun dari protein globin dan heme. Radikal bebas dapat menyebabkan lisisnya membran eritrosit. Proses tersebut dapat dicegah dengan pemberian antioksidan. Daun kelor termasuk dalam antioksidan alami yang memiliki sifat neurofektif melalui mekanisme antioksidatif. Mengetahui pengaruh pemberian ekstrak daun kelor (Moringa oleifera) Terhadap kadar hemoglobin pada tikus putih (Rattus norvegicus) galur Wistar jantan. Jenis penelitian eksperimental mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 14 Moringa oleifera leaves are an excellent source of iron (28.2 mg/100g), calcium (2003.0 mg/100g), vitamins A (16.3 mg/100g), B-complex, and C as well as minerals. 15 This plant has been recommended by the World Health Organization (WHO) and the United Nations (UN) as an alternative to dietary supplementation in meeting nutritional requirements. 16 , 17 Several studies have been conducted to prove the efficacy of Moringa leaves such as anti-inflammatory, analgesic, antipyretic, antihypertensives, wound healing, anti-diabetic, antiasthma, anticancer, anti-arthritis, anti-epileptic, antiviral, antianemia, and many more.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Moringa oleifera leaves are an excellent source of iron (28.2 mg/100g), calcium (2003.0 mg/100g), vitamins A (16.3 mg/100g), B-complex, and C as well as minerals. 15 This plant has been recommended by the World Health Organization (WHO) and the United Nations (UN) as an alternative to dietary supplementation in meeting nutritional requirements. 16 , 17 Several studies have been conducted to prove the efficacy of Moringa leaves such as anti-inflammatory, analgesic, antipyretic, antihypertensives, wound healing, anti-diabetic, antiasthma, anticancer, anti-arthritis, anti-epileptic, antiviral, antianemia, and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Astawan et al's research on the hematological features of white mice (Rattus norvegicus) infected with E. coli showed that there was an increase in the number of leukocytes and a decrease in the number of platelets due to E. coli (Astawan, 2011). Yesi et al's research on the effect of giving Moringa leaf extract on hemoglobin levels in male Wistar white rats revealed that there was an influence on hemoglobin levels in rats given Moringa leaf extract (Nurmalasari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin plays a role in improving the body's capillary function and increasing the ability to absorb vitamin C, vitamin C helps the absorption of iron, if the administration of iron is maximal, the production of blood in hemoglobin will increase (Nurmalasari, 2020).…”
mentioning
confidence: 99%